Melatonin protects cardiac microvasculature against ischemia/reperfusion injury via suppression of mitochondrial fission‐VDAC1‐HK2‐mPTP‐mitophagy axis. Issue 1 (27th April 2017) - Zhou, Hao; Zhang, Ying; Hu, Shunying; Shi, Chen; Zhu, Pingjun; Ma, Qiang; Jin, Qinhua; Cao, Feng; Tian, Feng; Chen, Yundai
Abstract: The cardiac microvascular system, which is primarily composed of monolayer endothelial cells, is the site of blood supply and nutrient exchange to cardiomyocytes. However, microvascular ischemia/reperfusion injury (IRI) following percutaneous coronary intervention is a woefully neglected topic, and few strategies are available to reverse such pathologies. Here, we studied the effects of melatonin on microcirculation IRI and elucidated the underlying mechanism. Melatonin markedly reduced infarcted area, improved cardiac function, restored blood flow, and lower microcirculation perfusion defects. Histological analysis showed that cardiac microcirculation endothelial cells (CMEC) in melatonin‐treated mice had an unbroken endothelial barrier, increased endothelial nitric oxide synthase expression, unobstructed lumen, reduced inflammatory cell infiltration, and less endothelial damage. In contrast, AMP‐activated protein kinase α (AMPKα) deficiency abolished the beneficial effects of melatonin on microvasculature. In vitro, IRI activated dynamin‐related protein 1 (Drp1)‐dependent mitochondrial fission, which subsequently induced voltage‐dependent anion channel 1 (VDAC1) oligomerization, hexokinase 2 (HK2) liberation, mitochondrial permeability transition pore (mPTP) opening, PINK1/Parkin upregulation, and ultimately mitophagy‐mediated CMEC death. However, melatonin strengthened CMEC survival via activation of AMPKα, followed by p‐Drp1 S616 downregulation and p‐Drp1 S37 upregulation, which blunted Drp1‐dependent mitochondrial fission. Suppression of mitochondrial fission by melatonin recovered VDAC1‐HK2 interaction that prevented mPTP opening and PINK1/Parkin activation, eventually blocking mitophagy‐mediated cellular death. In summary, this study confirmed that melatonin protects cardiac microvasculature against IRI. The underlying mechanism may be attributed to the inhibitory effects of melatonin on mitochondrial fission‐VDAC1‐HK2‐mPTP‐mitophagy axis via activation of AMPKα.